Islam and Scholarship Tradition: Historical Trajectories and Future Challenges of Modernity - Fadel, Mohammad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
Various forms of modernity that appear in phenomena of secularism, capitalism, and democracy have been penetrating Muslim lives. These social, economic, and political phenomena not only bring opportunities for a human betterment but also challenges to Islamic tradition and community. Muslim scholars and prominent figures offer different ways of how to deal with modernity and its challenges, ranging from adopting modernity while disregarding Islamic tradition, clinging to Islamic tradition and rejecting modernity, to selecting useful aspects of modernity and Islam to adapt to new circumstances. In this regard, this paper aims to address the question of what the modern challenges are, how Islam and Muslims deal with them, and what aspects of Islamic tradition that can be adopted to navigate multiple challenges of modernity. Through a critical reading of contemporary studies on religion and modernity and an analysis of Islamic scholarship and legal tradition, this paper argues that Islamic traditional scholarships provide Muslims with reliable tools to address challenges of modernity through the spirit of epistemic responsibility, Islamic virtues which includes honesty, respect for evidence, and acting for the benefit of others, civic virtue, and critical thinking skills.